INTEGRASI ASESMEN FORMATIF DALAM DESAIN LEMBAR KERJA PESERTA DIDIK UNTUK PEMBELAJARAN SISWA SEKOLAH DASAR - Novita Fitrotun Ni'mah (PT. Media Akademik Publisher, 2025)
This study examines the integration of formative assessment in the design of student worksheets to improve elementary school students’ learning, conducted at SD 6 Gondosari. The research addresses the issue of limited student engagement and insufficient comprehension in the learning process. The primary objective is to determine how the integration of formative assessment into worksheet design can enhance student learning outcomes. This research uses a qualitative approach with descriptive methods, involving observation, interviews, and documentation techniques to collect data. The data were analyzed through reduction, display, and conclusion drawing. The results show that student worksheets embedded with formative assessments support active learning, provide continuous feedback, and increase student participation and understanding. This study highlights the theoretical and practical significance of formative assessment implementation in elementary education and encourages teachers to incorporate it systematically in instructional design.